A time-use study of community health worker service activities in three rural districts of Tanzania (Rufiji, Ulanga and Kilombero). Issue 1 (December 2016) - Tani, Kassimu; Stone, Allison; Exavery, Amon; Njozi, Mustafa; Baynes, Colin; Phillips, James; Kanté, Almamy
Abstract Background Despite expanding international commitment to community health worker (CHW) deployment, little is known about how such workers actually use their time. This paper investigates this issue for paid CHWs named "Community Health Agents, " which in Swahili is "Wawezeshaji wa Afya ya Jamii" ("WAJA "), trained for 9 months in primary health care service delivery and deployed to villages as subjects of a randomized trial of their impact on childhood survival in three rural districts of Tanzania. Methods To capture information about time allocation, 30WAJA were observed during conventional working hours by research assistants for 5 days each over a period of 4 weeks. Results were presented in term of percentage time allocation for direct client treatment, documentation activities, health education, health promotion non-work-related activities and personal activities. Results During routine 8-h workdays, 59.5 % ofWAJA time was spent on the provision of health services and other work-related activities. Overall, WAJA spent 27.8 % of their work on traveling from home to home, 33.1 % on health education, 9.9 % of health promotion and only 12.3 % on direct patient care. Other activities related to documentation (7.8 %) and supervision (2.5 %). Conclusions Results reflect the pressing obligations ofWAJA to engage in activities other than direct work responsibilities during routine work hours. Time spent on work activities is primarily used for health education, promotion, moving between households, and direct patient care. However, greater effort should be directed to strengthening supervisory systems and follow-up of challengesWAJAs facing in order to increase proportion of working hours.